Anxiety and Attentional Bias in Children with Specific Learning Disorders - Haft, Stephanie L. (J Abnorm Child Psychol, 2019)
Children with specific learning disorders (SLDs) face a unique set of socio-emotional challenges as a result of their academic difficulties. Although a higher prevalence of anxiety in children with SLD is often reported, there is currently no research on cognitive mechanisms underlying this anxiety. One way to elucidate these mechanisms is to investigate attentional bias to threatening stimuli using a dot-probe paradigm. Our study compared children ages 9–16 with SLD (n=48) to typically-developing (TD) controls (n=33) on their attentional biases to stimuli related to general threats, reading, and stereotypes of SLD. We found a significant threat bias away from reading-related stimuli in the SLD, but not TD group. This attentional bias was not observed with the general threat and stereotype stimuli. Further, children with SLD reported greater anxiety compared to TD children. These results suggest that children with SLD experience greater anxiety, which may partially stem from reading specifically. The finding of avoidance rather than vigilance to reading stimuli indicates the use of more top-down attentional control. This work has important implications for therapeutic approaches to anxiety in children with SLD and highlights the need for attention to socio-emotional difficulties in this population. Future research is needed to further investigate the cognitive aspects of socio-emotional difficulties in children with SLD, as well as how this may impact academic outcomes.